“Determinación de dos propiedades termofísicas para la congelación de dos frutas tropicales: Arazá ( Eugenia stipitata me vaugh) en la Región San Martín - Flores García, Abner (2000)
The present paper is based on determination of thermophysics properties of Araza (Eugenia stipitata lvfo.Vaugh) and Pomarrosa (Sisigiam jambos Alston) fruits, with relationship it freezThe fruits were obtained from Tarapoto city, Province and Region of San Martín. The ripeness index, observed when the pulp both fruits on pressure by hand that notified soft and bland, characteristic color to mature state and proper aroma of ripe fruit. Araza fruit used presents a diameter between 8 to 12 cm., weight 180 g., yield in pulp 77,30% and pH: 3; Pomarrosa fruit a diameter 4 to 7 cm.; heiht 6 to 8 cm.; weight 7 6 g.; yield in pulp 72. 77% andpH :4,3. The aproximate chemical composition presented following content for both Araza and Pomarrosa; moisture: 86,84% and 85,40%; protein: 0,59% and 0,98%; fat: 1,59% and 0,92%; ash: 0,99% and O, 77% and carbohydrate: 9,89% and 11,93% respectively. By these approximate chemical conditions it obtained the :freezing initial point for Araza - 1.2ºC and Pomarrosa -l.6ºC, starting this and using SCHW ARTZBERG (1981) and CHEN (1985) equations, it got values b ( relationship binded water mass) of Araza 0,29 and Pomarrosa 0,225 Ms ( relationship e:ffective molecular weight) of Araza 310 and Pomarrosa 247,18 and E ( relationship water molecular weight between e:ffective molecular weight of solids) 0,05804 for Araza and Pomarrosa O, 072. The prediced curves of ice content, apparent specific heat and enthalpy as much Araza as Pomarrosa, present similar behaviours to indicated by in another fruits reported by RIEDEL (1956), HELDMAN (1982), HSIEH et al (1977), GONZALES (1991), presenting an acceptable concord with estímate values by SCHW ARTZBERG ( 1976, 1981) and CHEN (1985) equations. Likewise the encountered freezing curves, present the typical behaviour for de foods.